Changes in Rainfall Intensity, Rising Air Temperature, Wind Speed, and Its Relationship with Land Use in Makassar City - D., Didiharyono; Giarno, Giarno; Sapareng, Sukriming (Universitas Pendidikan Ganesha, 2022)
Makassar City is one of the big cities that is growing very rapidly in Indonesia which has a large coastal area. This city is very vulnerable to the impact of changes in climate variables such as rainfall, temperature and wind speed, especially when there are indications of massive land use changes. The aim of the research is to identify changes in the trend of high-intensity rainfall, changes in air temperature, wind speed, and their relationship to changes in land use in Makassar City which have an impact on climate change. Observation data at Maritime Meteorological Station of Paotere, Makassar for 30 years is used to detect changes in climate variables by using slope calculations on linear equations, line graphs, and boxplots. The results showed that the air temperature in Makassar has a lower increasing (0.06oC/year) than Indonesian region which is around 0.3 oC. The slope values at 07.00 WITA, 13.00 WITA, and 18.00 WITA representing temperatures in the morning, afternoon, and evening are 0.0387, 0.0476, and 0.0417. While the average slope of air temperature is 0.042. However, Rising of air temperature is followed by a decrease in the accumulation of annual rainfall to below 3000 mm/year. In addition, heavy rains that cause flooding, increasing the maximum wind speed also need to be observed because wind speed is one of the causes of hydrometeorological disasters that often occur.